The Effect Of Handwriting And Typing On Students’ Writing Skills - Siska Siska; Khaerun Nisa'a Tasyibu; Firdha Razak (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
The advent of the digital age has brought about a shift from handwriting to typing using digital devices. This change has raised concerns about its impact on writing skills. This study aims to analyze the effect of handwriting and typing on students' writing skills. A quantitative pre-experimental research method was used, involving two writing groups (handwriting and typing). Data were collected through writing skill tests and observation sheets, then analyzed using normality tests, homogeneity tests, and t-tests (independent sample t-tests). The results showed that handwriting had an effect on writing skills with an average score of 82.55, while typing also had an effect with an average score of 70.14. These findings indicate that handwriting has a greater influence than typing on writing skills. Students who write by hand produce more structured writing in terms of idea organization, grammar, spelling, and punctuation. Meanwhile, typing helps with writing speed, but is lacking in terms of idea processing and writing structure.